Childhood Langerhans Cell Histiocytosis: A ten-year study from Pakistan - Natasha Baig; Muhammad Rafie Raza; Nida Zia; Sidra Maqsood; Nausheen Yaqoob; Muhammad Shamvil Ashraf (Elsevier, 2022)
Introduction: Between 2 and 9 children per million per year are affected by Langerhans Cell Histiocytosis (LCH) globally. Despite aggressive treatment, mortality and reactivation rates for multisystem LCH remain above 20% and 30%, respectively. In low-middle income countries the problem is compounded by late presentation and diagnosis. Methods: A retrospective study was conducted by the Pediatric Hematology and Oncology Department at Indus Hospital and Health Network in Pakistan. Children 0 to 16 years with biopsy-proven LCH who presented between 2009 and 2019 were enrolled. Results: Forty-six patients were included, with a 59% male predominance. Thirty-two children had single system and 14 had multisystem LCH (64% with risk organ involvement). LCH-III protocol was administered to 17 and LCH-IV to 25. Relapse was observed in 12 patients; 8 were treated with modified salvage protocol, 3 with salvage protocol and 1 with LCH-III protocol. Two patients had progression of disease, 1 transformed to Hodgkin lymphoma and 1 developed non-Hodgkin lymphoma as a second malignancy. Over one-third of the patients expired. Conclusion: Further therapies must be developed to decrease LCH relapse rates and improve survival. Pakistan is subject to challenges, including malnutrition and treatment abandonment, that must be tackled to improve outcomes of children with cancer.